Initial Exploration of Career Awareness of Pre-School and Elementary School Children in Elementary School Career Guidance: A Limited Phenomenological Study - Cucu Arumsari; Eko Yulianto; Gina Sugiana Sugara (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the Study: To explore early childhood experiences in PAUD and elementary school (SD) that contribute to children's initial awareness and understanding of careers in the context of school-based career guidance. Methodology: Qualitative approach, phenomenological design; tools: semi-structured interviews, direct observation, documentation; analysis method: Colaizzi; participants: two purposively selected children aged 4 and 9; software/tools: manual coding without specific software; data sources: children's verbal responses, behavior, and creative work. Main Findings: Children’s career ideals shaped by visual media, direct experience, and close environment; understanding of work remains basic but developing; schools introduce careers through role-play and visual aids; parents support awareness via play tools and discussion. Four main thematic findings emerged highlighting the importance of combined school-family efforts. Novelty/Originality of this Study: This study uniquely captures early career awareness from children’s perspectives using phenomenological analysis. It introduces fresh insights into how early education environments and families collaboratively shape initial career concepts, offering foundational input for developing contextualized, age-appropriate career guidance in elementary education.